1995
DOI: 10.1093/oxfordjournals.humrep.a135842
|View full text |Cite
|
Sign up to set email alerts
|

The probability of pregnancy after embryo transfer is affected by the age of the patient, cause of infertility, number of embryos transferred and the average morphology score, as revealed by multiple logistic regression analysis

Abstract: Because the process of conception is affected by many variables, a multiple logistic regression analysis was performed to assess (i) the impact and relative weight of both patient and embryo variables and (ii) their possible effects on the probability of a vital pregnancy after embryo transfer. A statistical model was constructed predicting the probability of pregnancy after embryo transfer. The variables that contributed significantly to the predictive value of the model were the age of the patient, the cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
1
4

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(68 citation statements)
references
References 0 publications
4
59
1
4
Order By: Relevance
“…By the two sample Student'st-test (http://www.usablestats.com/calcs/ 2samplet&summary01), this difference was significant (p00.0088). That the age of the woman is inversely related to the success of the IVF-ET procedure had been established previously (see, for example, [12]). …”
Section: Ivf-et Patients and Their Outcomesmentioning
confidence: 56%
“…By the two sample Student'st-test (http://www.usablestats.com/calcs/ 2samplet&summary01), this difference was significant (p00.0088). That the age of the woman is inversely related to the success of the IVF-ET procedure had been established previously (see, for example, [12]). …”
Section: Ivf-et Patients and Their Outcomesmentioning
confidence: 56%
“…Therefore, these cutoff points should not be consid ered too strictly. The authors of a recent study on standard IVF reported that they could not demon strate a change in age effect (25). However, as they included age only as a (log)linear variable in the model, it was not possible (by definition) to find a change in trend.…”
Section: Discussionmentioning
confidence: 97%
“…This has largely been attributed to variables such as the patient's age, endometrial receptivity, embryo quality [1,2] and embryo transfer technique per se [3][4][5]. As in vitro fertilization treatment (IVF) involves the placement of embryos into the uterine cavity using a catheter that passes through the cervix, the possibility of bacterial contamination during the embryo transfer procedure clearly exists, but has been poorly explored.…”
Section: Introductionmentioning
confidence: 99%